Thrombopoietin receptor agonists in patients with persistent or chronic immune thrombocytopenia. (15th January 2018) - Agnelli Giacchello, Jacopo; Valeri, Federica; Boccadoro, Mario; Borchiellini, Alessandra
Abstract: Objectives: To assess long‐term treatment patterns and outcomes in patients with persistent or chronic immune thrombocytopenia (ITP), also considering the impact of the treatment with thrombopoietin receptor agonists (TPO‐RAs) prior to splenectomy. Methods: Medical records of all patients with persistent or chronic ITP seen at our institution between January 1985 and December 2016 were reviewed. Data on demographic and clinical characteristics were analyzed using descriptive statistics. Wilcoxon rank‐sum test was used to compare medians between groups of patients. Results: Among 80 patients with persistent or chronic ITP, 34 underwent splenectomy and 59 were treated with TPO‐RAs. Twenty patients were both splenectomized and treated with TPO‐RAs; among them, 9 received TPO‐RAs before splenectomy. Median time to splenectomy from diagnosis of ITP was 25 months in the group of patients pretreated with TPO‐RAs vs 14.5 months in the group of splenectomized patients. These differences were not statistically significant. Conclusions: Our study provides some initial data on the potential benefits of the treatment with TPO‐RAs that may allow splenectomy to be safely deferred for prolonged periods. More research is needed to evaluate the impact of the treatment with TPO‐RAs prior to splenectomy.